MEDIA PEMBELAJARAN BERBASIS VIDEO TUTORIAL PADA MATA KULIAH TATA RIAS PENGANTIN BALI - Ida Ayu Reviena Damasanti; Widiartini, Ni Ketut (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
The use of video tutorial supports the practicum in the learning process. The present study developed a video tutorial on Agung Khas Buleleng bridal makeup as learning media for Balinese bridal makeup courses. This study was designed in research and development (Research & Development) using the ADDIE model. This study involved 4 lecturers teaching Balinese bridal makeup courses, 12 students taking Balinese bridal makeup courses, and 4 experts. This study used three instruments, namely interview guides, questionnaires, and checklist sheets. The data collected were analyzed qualitatively and quantitatively. The results of the study show namely (1) Students who take part in the process of learning Balinese bridal make-up need learning media in an audio-visual form that is authentic and presents the steps for facial make-up, hair make-up, and Balinese bridal fashion using Payas Agung Khas Buleleng; (2) The development of the Bali Payas Agung Khas Buleleng bridal make-up video tutorial was carried out by adapting the ADDIE model, namely analysis, design, development, implementation, and evaluation; (3) Evaluation shows that the product developed has a good level of feasibility and gets a positive response from students.